The Politicisation of migration - Brug, Wouter van der (London Routledge, 2015)
"Why are migration policies sometimes heavily contested and high on the political agenda? And why do they, at other moments and in other countries, hardly lead to much public debate? The entrance and settlement of migrants in Western Europe has prompted various political reactions. In some countries anti-immigration parties have gained substantial public support while in others migration policies have been hardly controversial. The Politicisation of Migration examines the differences between seven Western European countries by developing a conceptual framework to empirically explain patterns of politicisation and de-politicisation. The analyses show that over the past decade immigration has been increasingly defined in socio-cultural terms and that it has been receiving less political attention since the economic crisis started in 2007. This book also looks at the role of mainstream parties and political actors in the process of politicisation, and demonstrates how the role of 'challengers' is more limited than often assumed. Contributing to literatures on migration, party politics and agenda-setting, the book will be of interest to students and scholars in the fields of politics and migration studies"-- Provided by publisher.
A framework for studying the politicisation of immigration / Wouter van der Brug, Gianni D'Amato, Joost Berkhout and Didier Ruedin -- Research design / Joost Berkhout, Didier Ruedin, Wouter van der Brug and Gianni D'Amato -- Politicisation of immigration in Austria / Sarah Meyer and Sieglinde Rosenberger -- The politicisation of immigration in Belgium / Guido Vangoidsenhoven and Jean-Benoit Pilet -- The politicisation of immigration in Ireland / Kevin Cunningham -- The politicisation of immigration in the Netherlands / Joost Berkhout, Laura Sudulich and Wouter van der Brug -- The politicisation of immigration in Spain / Virginia Ros and Laura Morales -- Politicisation of Immigration in Switzerland : the importance of direct democracy / Didier Ruedin and Gianni D'Amato -- The politicisation of immigration in Britain / João Carvalho, Roger Eatwell, Daniel Wunderlich -- Cross-country comparisons and conclusions / Wouter van der Brug, Didier Ruedin , Joost Berkhout and Kevin Cunningham.
Includes bibliographical references and index.
Keywords: Europe -- Emigration and immigration -- Political aspects; Europe -- Emigration and immigration -- Government policy; Europe -- Emigration and immigration -- Political aspects -- Case studies; Europe -- Emigration and immigration -- Government policy -- Case studies